Sequência didática de magnetismo: uma proposta para o ensino de alunos com TDA - Vasconcelos, Adriano Henrique de (2021)
This work seeks to supply the need to insert students who have Attention Deficit Disorder (ADD) in the educational scope by making an educational product composed of a set of didactic sequences based on the significant learning of David Ausubel. In the search for the insertion of these people with disabilities in the teaching and learning process and in line with one of the lines of research and development of the National Professional Master in Physics Teaching (MNPEF / SBF). We designed this project in order to contribute to improving the teaching-learning process of these students, in accordance with the legal requirements of social inclusion in force. The inclusion of students with disabilities in mainstream schools is enshrined in the legal texts, however, inclusive education is not limited to observance of the law that recognizes and guarantees it, but requires a change in the attitude, perception and conception of educational systems. This work brings didactic tools materialized in didactic sequences to be used with high school students with such learning needs, in order to offer a pedagogical tool that facilitates learning in the classroom, of students with learning disabilities, specifically at this level . This project aims to bring to the classroom a content of theoretical and experimental Magnetism, where the practical part aims to consolidate the theory seen in the classroom. The experiments are adapted to the student's reality and their daily lives, in order to present new teaching methods that bring diversification of the students' learning.